Off-Shore Fly or Die Holograms for Desert Locust Swarms - Sevilmis, Ugur (My University, 2020)
A random walk search was conducted on academic papers to find a method for ecological combat of desert locust. Relatedness of papers and concepts were mainly analysed with the core idea of “Fighting Rooster” vs “Desert Locust “ interspecies competition. It was interesting to find a better preator than fighting roosters for locust swarms in the sea. Usage of a technology is required in this theoric approach to modify collective behavior of desert locusts which looks like the achilles heel of swarms.
Keywords: collective intelligence; interspecies competition; Invasion; migration; multi-species communities; predation; süper-organism; swarm intelligence